Analysis Of Accuracy Of Cjs Patient Diagnosis Code In Buayan Health Center On The Outdoor Diagnosis Of Pku Muhammadiyah Gombong - PUTRI APRILIANA WULANDARI PUTRI APRILIANA WULANDARI (Health Media, 2021)
The purpose of this study was to obtain an analysis of the accuracy of the reference diagnosis code for BPJS patients at the Buayan health center to diagnose out of PKU Muhammadiyah Gombong hospital. This research was conducted at the Buayan Health Center and PKU Muhammadiyah Gombong, in the medical record sub-section. This study uses descriptive quantitative methods, samples taken by means of sample random sampling and using linear regression. Based on the results of the study and the discussion of the accuracy of the reference diagnostic code for BPJS patients at the Buayan Community Health Center as much as 40 (64.5%), the inaccuracy of the reference diagnosis codes for BPJS patients at the Buayan Health Center was 22 (35.5%). The exact outpatient diagnosis of PKU Muhammadiyah Gombong was 40 (64.5%), while inaccurate diagnoses of PKU Muhammadiyah Gombong were 22 (35.5%). While the results of a simple linear regression analysis of the accuracy of the reference diagnosis code for BPJS patients at the Buayan Community Health Center on the outgoing diagnosis of PKU Muhammadiyah Gombong obtained a significance value of 0,000. The signification value is <0.1, meaning that Ho is rejected and H1 is accepted so that there is an influence between the accuracy of the reference diagnosis code of BPJS patients at the Buayan Community Health Center on the outgoing diagnosis of PKU Muhammadiyah Gombong.